Arduino-Based Multifunctional Rack as a HSE Learning Aid in the Polimedia Graphic Laboratory - Besse Irna Tawaddud (Jurnal Ilmiah Publipreneur, 2020)
Based on Undang-Undang Kesehatan No. 36/2009 that HSE efforts must be carried out in all workplaces including in the learning process involving humans and technology, including laboratories. HSE Learning and Environmental Management are still not applied in doing graphic practicum. The application and understanding of OSH are needed as character development for the study of Graphic DIII in the 4.0 era. This study aims to design learning aid based on Arduino Graphics so as to increase students' understanding and awareness of the application of HSE culture. The method used is Research and Development. The results of this study obtained a multifunctional rack for storage of supporting components in HSE and Environmental Management Learning in the Arduino-based Graphic Laboratory to be able to detect obstacles. Further research and testing still needs to be done. Further research and testing still needs to be done.